1989
DOI: 10.1111/j.1540-8159.1989.tb02678.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiologic Evaluation of Asymptomatic Patients with the Wolff‐Parkinson‐White Pattern

Abstract: In the past 4 years, 34 asymptomatic patients with the Wolff-Parkinson-White (WPW) pattern underwent electrophysiologic study. The effective refractory period (ERP) of antegrade conduction over the accessory pathway was 288 +/- 29 msec. In three asymptomatic patients (9%), the antegrade ERP of the accessory pathway was shorter than 250 msec. The antegrade ERP of the accessory pathway became shorter than 250 msec in an additional 12 of 22 (55%) patients after isoproterenol administration. Nineteen (56%) of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 14 publications
0
23
0
1
Order By: Relevance
“…[12][13][14][15][16][17][18][19][20][21] Recent data have challenged the assumption that the asymptomatic WPW population is at minimal or no risk of sudden death and that RFA can be of benefit in asymptomatic subjects at risk. [21][22][23][24][25][26][27] The purpose of this study was to evaluate the long-term outcomes and predictors in a large cohort of symptomatic or asymptomatic WPW patients undergoing electrophysiological testing (EPT) using a prospective patient registry.…”
Section: September 2 2014mentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20][21] Recent data have challenged the assumption that the asymptomatic WPW population is at minimal or no risk of sudden death and that RFA can be of benefit in asymptomatic subjects at risk. [21][22][23][24][25][26][27] The purpose of this study was to evaluate the long-term outcomes and predictors in a large cohort of symptomatic or asymptomatic WPW patients undergoing electrophysiological testing (EPT) using a prospective patient registry.…”
Section: September 2 2014mentioning
confidence: 99%
“…In studies reporting a mean age, the range was 32 to 50 years, [17][18][19][20]22,23 and in studies reporting a median age, the range was 19 to 36 years. [15][16][17] The majority of patients were male (range 50% to 74%).…”
Section: Study and Patient Characteristicsmentioning
confidence: 99%
“…15,16,[18][19][20][21][22][23] These 9 studies contributed data from 1818 participants (although some patients were included in >1 study), with sample sizes ranging from 29 to 550 asymptomatic patients with no ablation of the accessory pathway and from 37 to 206 asymptomatic patients with ablation of the accessory pathway. [17][18][19][20][21][22][23] All 9 studies addressed question 3, which examined the usefulness of either invasive EP study without catheter ablation of the accessory pathway or noninvasive EP study for predicting arrhythmic events in patients with asymptomatic pre-excitation.…”
Section: Study and Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…120, 121 Patients at a high risk of transition from atrial fibrillation to VF may be identified on the basis of the refractory period of antegrade conduction over the accessory pathway or the shortest R-R interval during atrial fibrillation induced during EPS. 118,122, 123 …”
Section: Wolff-parkinson-white Syndromementioning
confidence: 99%